DISTRIBUSI HARA DALAM TANAH DAN PRODUKSI AKAR TANAMAN KELAPA SAWIT PADA METODE PEMUPUKAN YANG BERBEDA - Edy Sigit Sutarta; Winarna; Muhammad Arif Yusuf (Talenta Publisher, 2017)
The effectiveness of fertilization could be influenced by the type of fertilizer and the rightmethod. There are several methods of fertilization, such as fertilizer applied in pockets andscattered. Relations fertilization method with root distribution of oil palm plantations andnutrients in the soil need to be known, so it can be determined in a more effective method offertilization for oil palm plantations. The observation was performed 1 year after application,includes observation of the soil (physical and chemical properties) and the observation of theroot (primary root, secondary, tertiary). Examples of soil and roots were taken at depths of00-20 cm, 20-40 cm, 40-60 cm, 60-80 cm, and 80-100 cm at a distance of 50 cm, 100 cm,150 cm, 200 cm, 250 cm, 300 cm, 350 cm, 400 cm from the base of the stem. The resultsshowed that the distribution of nutrients in the soil surface is greater than the layerunderneath and root production decreased due to lower soil layers.